Interfacing native and non-native peptides: using Affimers to recognise α-helix mimicking foldamers - Arrata,I; Barnard,A; Tomlinson,DC; Wilson,AJ (Chemical Communications, 2017)
Selection methods are used to identify Affimers that recognise α-helix mimicking N-alkylated aromatic oligoamides thus demonstrating foldamer and natural α-amino acid codes are compatible.